KAJIAN POTENSI EKOWISATA BAHARI KENAGARIAN MANDEH KECAMATAN KOTO XI TERUSAN KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - Fuadi, Kelly; Yoswaty, Dessy; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in March 2016 in the District of Region IX Kenagarian Mandeh Koto Tarusan South Pesisir regency of West Sumatra Province. The sample selection for the interviews were done using purposive sampling method, for the determination of travelers sample performed by accidental sampling method.Potential economic value of marine tourism in Kenagarian Mandeh in 2015 amounted Rp.14.751.669.500,00-. Based on the suitability of the development of nautical tourism is very fit, well judged based on the criteria supporting tours, WTA and WTP calculation of the value, the calculation of the potential economic value, through a SWOT analysis. So Kenagarian Mandeh potential to be developed into a marine ecotourism areaKeywords: Kenagarian Mandeh, Ecoutourism Potential.